SOLAR ENERGY ADAPTATION AND EFFICIENCY ACROSS DIVERSE NIGERIAN AND GLOBAL CLIMATES: A REVIEW OF TECHNOLOGICAL ADVANCEMENT - Gabriel Gbenga Ojo; Oluwaseun Augustine Lottu; Tina Chinyere Ndiwe; Uchenna Izuka; Nwakamma Ninduwezuor-Ehiobu (Engineering Heritage Journal)
Solar energy stands as a transformative force in addressing the world’s energy needs while mitigating the effects of climate change. This comprehensive review paper explores solar energy adaptation and efficiency across diverse climates, focusing on Nigeria, a nation grappling with energy access disparities and environmental challenges. The paper surveys technological advancements, climate-specific considerations, policy and regulation, environmental and economic impacts, challenges, and future directions in solar energy. Real-world case studies from rural Nigeria to Canada illustrate the versatility of solar technologies, while policy frameworks and regulatory approaches are analyzed to provide insights into effective solar energy promotion. The paper underscores the interconnected nature of environmental and economic benefits. It emphasizes the importance of tailored solutions and community engagement. Technological innovation, policy alignment, and capacity building address challenges such as intermittency, climate-related factors, and upfront costs. Future directions emphasize technological innovation, policy alignment, energy access, capacity building, international collaboration, public awareness, and monitoring and evaluation. As Nigeria and the world navigate a sustainable and solar-powered future, the sun emerges as a boundless energy source, illuminating homes, powering industries, and fueling economic growth while preserving the environment for future generations.